2009
DOI: 10.1017/s1461145709000091
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in depressive patients with gastric adenocarcinoma

Abstract: Recent data from several studies suggest that oxidative stress is involved in the biochemical mechanisms that underlie neuropsychiatric disorders. The present study was designed to investigate oxidative stress status in depressive patients with gastric adenocarcinoma (GA) at TNM stage III. Oxidative stress, depression and expression of specific genes were monitored during a pretreatment period. Serum total antioxidant capacity, catalase, superoxide dismutase concentrations, and antisuperoxide anion capacity (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…In the case of SOD and GPx, there are also some discrepancies between studies. Some of them confirm a link between depression and increased activity of SOD (Wei et al 2009, Sarandol et al 2007). Some researchers confirmed that the occurrence of depression was associated with excessive activity of Gpx (Bilici et al 2001); while others did not detect any difference between the study and control groups (Kotan et al 2011, Kodydkova et al 2009).…”
Section: Oxidative and Nitrosative Stress In The Development Of Deprementioning
confidence: 88%
See 1 more Smart Citation
“…In the case of SOD and GPx, there are also some discrepancies between studies. Some of them confirm a link between depression and increased activity of SOD (Wei et al 2009, Sarandol et al 2007). Some researchers confirmed that the occurrence of depression was associated with excessive activity of Gpx (Bilici et al 2001); while others did not detect any difference between the study and control groups (Kotan et al 2011, Kodydkova et al 2009).…”
Section: Oxidative and Nitrosative Stress In The Development Of Deprementioning
confidence: 88%
“…In addition, some inaccuracies may arise from size differences of the studied groups, environmental impacts and the severity of the disease. Furthermore, patients with depression are characterized by decreased activity of glutathione peroxidase (GPx) and increased activity of xanthine oxidase (Ox), an enzyme responsible for the production of hydrogen peroxide and superoxide anion, and superoxide dismutase (SOD) (Maes et al 2011a, Wei et al 2009). In the case of SOD and GPx, there are also some discrepancies between studies.…”
Section: Oxidative and Nitrosative Stress In The Development Of Deprementioning
confidence: 99%
“…Elevated MDA levels have also been confirmed in depressed patients suffering from chronic heart failure (Michalakeas et al, 2011) and newly diagnosed gastric adenocarcinoma (Wei et al, 2009). …”
Section: Oxidative Stress and Antioxidant Defence Biomarkersmentioning
confidence: 93%
“…The power analysis was performed considering the results of a previous study [28] on this subject. We calculated a sample size of 20 patients in both the patient group and the control group for α = 0.05 and β = 0.20 with a power of 0.90 in a 2-tailed test.…”
Section: Methodsmentioning
confidence: 99%